Brand and firm value: Evidence from Arab emerging markets - Musaab Mousa; Judit Sági; Zoltán Zéman (Economies, 2021)
This study aims to estimate the impact of brand as the most important intangible marketing asset on firm value, measured by share return in some Arab emerging market, as well analyze the moderating role of agency costs in the relationship between share return and brand. We use the Ohlson model of valuation with a sample of the most traded companies on four markets under study. The panel data regression results show a significant impact of brand on return as well as agency costs that promote the valuation model power, meaning that good corporate governance increases the degree of marketing investment efficiency in value creation. Our findings support the literature relating to the residual earnings valuation model. Furthermore, the results confirm the informative content of marketing application besides the traditional accounting figures as a promising approach for firm valuation.
Keywords: 330; agency costs; brand equity; Ohlson model; share return